Pre-current amplifier based transimpedance amplifier for biosensors - Jyoti M. Roogi; Manju Devi (International Journal of Reconfigurable and Embedded Systems (IJRES), 2022)
In this paper, we present current amplifier based transimpedance amplifier (TIA) for biosensor applications. Proposed design has low-noise, high Transimpedance gain that can be used for low current measurement applications. The current amplifier based TIA is implemented in order to resolve the fabrication issues related to high value feedback resistor. In this design, the input block to TIA is a low amplitude current amplifier. The designed amplifier is implemented in 90 nm complementary metal-oxide semiconductor (CMOS) technology. The design achieves transimpedance gain of 800 kΩ with a bandwidth of 5 kHz and input referred current noise is of 0.152 pA/√???????? for an input of 41 nA bypassed from current amplifier with input of 200 pA.